2009
DOI: 10.1042/cs20080538
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the retinal microvasculature in European and African-Caribbean people with diabetes

Abstract: Diabetes aggravates the impact of elevated BP (blood pressure) on the microcirculation, and people of African ancestry with diabetes are more susceptible to microvascular damage than Europeans. In the present study, we investigated possible differences in the retinal microcirculation in people of European and African-Caribbean ethnicity with diabetes that might account for this. A total of 51 subjects with Type 2 diabetes (age 40–65 years; 25 male; 29 African-Caribbean) were studied. Clinic and 24 h ambulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…This was explained by their higher blood pressure, but it was also noted that diabetes influenced the relationship between blood pressure and arteriolar diameter. This is consistent with the findings of Mahal et al [35] who reported wider arteriolar calibre in African Caribbean people with diabetes than Europeans with diabetes. Similar observations showing an interaction between arteriolar calibre, diabetes and ethnicity have also been reported in MESA.…”
Section: Discussionsupporting
confidence: 93%
“…This was explained by their higher blood pressure, but it was also noted that diabetes influenced the relationship between blood pressure and arteriolar diameter. This is consistent with the findings of Mahal et al [35] who reported wider arteriolar calibre in African Caribbean people with diabetes than Europeans with diabetes. Similar observations showing an interaction between arteriolar calibre, diabetes and ethnicity have also been reported in MESA.…”
Section: Discussionsupporting
confidence: 93%
“…Disease duration has been previously shown to influence retinal arteriolar/venular diameter ratio in diabetic patients . Our observation that WT as well as CA, both parameters of hypertrophic remodeling, are related to diabetes duration indicates “disease duration” as an impact factor of retinal microvascular changes.…”
Section: Discussionmentioning
confidence: 52%
“…However, these differences were not independent of obesity, duration of diabetes and diabetes treatment and control [20]. Some recent studies have examined the retinal microvasculature directly [21–23], leading to suggestions that there may be increased susceptibility to microvascular damage in African Caribbeans [22].…”
Section: Discussionmentioning
confidence: 99%